Impact of Burnout Syndrome among Thai Neurosurgeons: Prevalence, Contributing Factors, and Consequences - Boontoterm, Panu; Urasyanandana, Karanarak; Fuengfoo, Pusit (Indian Journal of Neurosurgery, 2025)
Burnout syndrome (BOS) is a work-related condition characterized by emotional exhaustion, chronic stress, and a sense of disillusionment with one's profession. It is particularly prevalent among health care professionals, especially neurosurgeons, and has been linked to higher rates of resignation and reduced job satisfaction. However, the prevalence and impact of BOS specifically among Thai neurosurgeons have not been extensively studied.This study aims to evaluate the prevalence of BOS among Thai neurosurgeons and identify the key risk factors associated with its development.This was a multicenter, prospective cross-sectional study conducted across five hospitals in Thailand. Data on BOS were collected through electronic questionnaires administered to Thai neurosurgeons. BOS was assessed using the Maslach Burnout Inventory, which measures burnout across three key dimensions: depersonalization, emotional exhaustion, and reduced personal accomplishment. Variance inflation factors were calculated to assess multicollinearity and ensure the reliability of the logistic regression results.The overall prevalence of BOS among Thai neurosurgeons was found to be 52%. Multivariate analysis identified several significant risk factors for BOS, including age over 40 years, less than 5 years of experience in neurosurgery, perceived excessive workload, monthly income below 60,000 Baht, consideration of resignation in the past year, a need for more than 2 days of vacation per week, and patient length of stay exceeding 10 days.This study demonstrated a high prevalence of BOS among Thai neurosurgeons, emphasizing the urgent need for targeted interventions to prevent and address BOS within this group.
Keywords: burnout syndrome; emotion exhaustion; depersonalization; personal accomplishment; neurosurgeons